Evaluation of 2 ELISAs to determine Borrelia burgdorferi seropositivity in horses over a 12-month period. (July 2021) - Neely, Megan; Arroyo, Luis; Jardine, Claire; Clow, Katie; Moore, Alison; Hazlett, Murray; Weese, J. Scott
The blacklegged tick ( Ixodes scapularis ), which transmits Borrelia burgdorferi, the causative agent of Lyme disease, has undergone rapid range expansion in Ontario. In horses, Lyme disease remains an enigmatic disease, with limited understanding of the pathogenesis and many issues pertaining to selection and interpretation of laboratory tests. We evaluated B. burgdorferi seropositivity in naturally exposed horses over a 12-mo period and compared paired samples with 2 common serologic tests. Serum samples were collected in 2017, 1 y after initial testing, from a cohort of 22 horses that were seropositive in a 2016 seroprevalence study. Samples were tested using a C6 ELISA and a multiplex ELISA targeting outer surface proteins A, C, and F. 1 y after initial testing, 14 of 22 (64%) horses remained seropositive; 7 (32%) were positive on the multiplex ELISA, 2 (9%) on C6 ELISA, and 5 (23%) on both tests. Repeatability was 100% for the C6 ELISA, and 95% for the multiplex ELISA, with no significant difference between paired sample multiplex titer values. Our results indicate strong intra-test reliability, although further investigation is required to determine the clinical significance of serologic testing.